PERBANDINGAN BESAR GAYA PADA GIGI ANTARA PEMAKAIAN BRAKET ROTH KONVENSIONAL DAN SELF-LIGATING PADA EMPAT TINGKAT KEPARAHAN MALPOSISI GIGI (Kajian Pada Model Gigi Akrilik) - , ADITYA GUNGGA KUSUMADHARMAWASKITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Force is an action or actions that change, or have a tendency to change the state of the motionless became move. Application of force to the teeth is one of the important aspects of orthodontic treatment that causes tooth movement. This study aims to find out the difference between the force on the teeth using conventional Roth bracket and self-ligating Roth bracket at the four levels of severity of malposition. This study uses a metal Roth bracket 0.022 inch slot consisting of conventional bracket and self-ligating bracket. Bracket attached to the 8 acrylic replica of typodont which has been prepared on the terms of the severity of malposition. Value of foce is measured using a Schlegel mathematical formula on second incisor, canine, and first premolar mandibular on bucco-lingual direction, inciso-gingival direction, and mesio-distal direction. The statistics analysis used are Two way Analisys of variance followed by post hoc test. The results showed that the value of the force on the mandibular second incisor, canine and first premolar on bucco-lingual direction, mesio-distal direction and inciso-gingival direction highest and lowest was obtained on the use of conventional Roth bracket. Two way ANOVA test results showed no significant difference (p> 0.05) the force on the teeth between the use conventional Roth braket and self-ligating Roth braket, there is difference in force because of increased severity of tooth malposition between the use of conventional Roth braket and self-ligating Roth braket (p <0.05), and there is no interaction (p> 0.05 ) between the use of conventional Roth braket and selfligating Roth bracket and increasing severity of dental malposition concerning to forces on the teeth. Keywords: force on the teeth, Roth conventional bracket, Roth self-ligating bracket, malposition of teeth